Cartel stability in an exhaustible resource model - Jonathan P. Thomas (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
A simple oligopolistic common-pool exhaustible resource game is considered. By analysing punishment strategies, including optimal punishments, it is possible to determine which cartel agreements are implementable in a non-cooperative play of the game. Joint-profit maximizing allocations are sustainable for sufficiently low discounting, but in general it is shown that no folk-theorem exists for this model. In particular, for sufficiently high elasticities of demand, it is shown that optimal punishments are not sufficiently severe to enforce stationary symmetric extraction paths, thus confirming the hypothesis that sufficient market power is needed for a cartel to be stable.
Keywords: 330